2017
DOI: 10.4081/ija.2017.958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of critical nitrogen and phosphorus models for maize under full and limited irrigation conditions

Abstract: Proper nitrogen (N) fertiliser application rates and timing of application, coupled with optimum irrigation management can improve the sustainability of maize production and reduce the risk of environmental contamination by nutrients. The impact of full and limited irrigation and rainfed conditions on in-season maize (Zea mays L.) shoot biomass nutrient concentration and critical N and phosphorus (P) indices were evaluated using a combination of measured nutrients and critical N and P models in south central N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Heckman et al [ 54 ] reported maize grain N, P, and K concentrations of 1.29, 0.38, and 0.48%, respectively, which are higher than the finding of the present study regardless of the planting density and the planting date. The decreasing trend of grain nutrients with plant density is the dilution effect [ 21 , 55 , 56 ]. Maize grain nutrient uptake increased with plant density and decreased after 88,000 pph like the findings of Raymond et al [ 21 ] who reported that maize grain N uptake increased with plant density up to 74,000 pph and decreased at the highest density.…”
Section: Discussionmentioning
confidence: 99%
“…Heckman et al [ 54 ] reported maize grain N, P, and K concentrations of 1.29, 0.38, and 0.48%, respectively, which are higher than the finding of the present study regardless of the planting density and the planting date. The decreasing trend of grain nutrients with plant density is the dilution effect [ 21 , 55 , 56 ]. Maize grain nutrient uptake increased with plant density and decreased after 88,000 pph like the findings of Raymond et al [ 21 ] who reported that maize grain N uptake increased with plant density up to 74,000 pph and decreased at the highest density.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the critical phosphorus concentration in plant tissues (P c ) of wheat calculated based on shoot biomass significantly differs among locations, whereas the location or region (Canada, Finland, and China) does not significantly affect this relationship if the P c is described as a function of the shoot nitrogen concentration [ 213 ]. Djaman and Irmak [ 214 ] further extended this procedure by calculating the critical phosphorus concentration in maize shoot biomass in combination with the critical nitrogen model (P c and N c ), resulting in a more robust tool for determining the critical nitrogen and phosphorus in maize. Most of the calculations of the dilution curves cover the nutrient concentration determined in the whole shoot biomass.…”
Section: Methods Related To the Specific Environments And Nutrients R...mentioning
confidence: 99%
“…Higher nutrient uptake levels have mainly been observed under adequate or fully irrigated conditions, while lower nutrient uptake is typical under water-limiting conditions ( Setiyono et al., 2010 ; Djaman et al., 2013 ; Faloye et al., 2019 ). For instance, Djaman and Irmak (2018) observed reduced nitrogen (N) uptake when corn was irrigated below 75% of fully-irrigated treatment, with the fully-irrigated treatment being irrigation scheduling at 60% of total available water. The authors observed similar results for phosphorus (P) ( Djaman and Irmak, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The root length and K influx were also reduced by about 50% under the low soil water conditions ( Seiffert et al., 1995 ). The lower nutrient uptake under water stress is usually due to decreased nutrient transport by mass flow and diffusion ( Seiffert et al., 1995 ; Buljovcic and Engels, 2001 ; Djaman and Irmak, 2018 ). Thus, nutrients that are preferentially taken up by the mass flow pathway tend to restrict plant growth the most under dry conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation